2019
DOI: 10.1016/j.apsb.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophanol protects against doxorubicin-induced cardiotoxicity by suppressing cellular PARylation

Abstract: The clinical application of doxorubicin (DOX) in cancer chemotherapy is limited by its life-threatening cardiotoxic effects. Chrysophanol (CHR), an anthraquinone compound isolated from the rhizome of Rheum palmatum L., is considered to play a broad role in a variety of biological processes. However, the effects of CHR׳s cardioprotection in DOX-induced cardiomyopathy is poorly understood. In this study, we found that the cardiac apoptosis, mitochondrial injury and cellular PARylation leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 55 publications
(129 reference statements)
1
34
0
Order By: Relevance
“…Due to its toxicity to normal tissues, its clinical applications have been greatly limited. Thus, in recent years, efforts have been made to study Dox delivery systems to deliver drugs and reduce its toxicity and side effects on normal cells 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its toxicity to normal tissues, its clinical applications have been greatly limited. Thus, in recent years, efforts have been made to study Dox delivery systems to deliver drugs and reduce its toxicity and side effects on normal cells 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…AST is a transaminase marker for detecting liver injury. 2,14 Aer liver cells are damaged, enzymes such as AST are released into the blood. Therefore, detection of AST activity in the serum can accurately reect the degree of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CC1 4 -induced liver injury can be regulated or even restored to normal levels by the scavenging free radical enzyme, SOD. 2,4 Therefore, the antioxidant effect of HFY06 can be determined by determining the levels these important antioxidant-related genes. Compared with the model group, high-dose HFY06 upregulated Cu/Zn-SOD, Mn-SOD, and CAT mRNA expression, indicating that the free radicals produced by CCl 4 -induced liver oxidative metabolism can be eliminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysophanol, a member of the anthraquinone family, is a plant-derived herbal drug that is well known for its strong anti-inflammatory, anti-mutagenic, anti-microbial, hepatoprotective, and anti-carcinogenic activities [ 12 , 13 ]. Emerging evidence demonstrates that chrysophanol can alleviate the development of cardiovascular complications, such as diabetic cardiomyopathy [ 14 ], doxorubicin-induced cardiotoxicity [ 15 ], and isoproterenol-induced cardiac hypertrophy [ 16 ]. These pre-clinical studies have suggested the potential therapeutic value of chrysophanol in treating cardiac disease.…”
Section: Introductionmentioning
confidence: 99%